Augmented reality marker-based technology for augmenting newspaper advertisement - Pervez, Rahat; Chowdhury, Diba; Sagor, Md Sahadat Hossain; Hoque, Md. Imdadul; Islam, Nafiul (Recent Research in Science and Technology, 2021)
In this research, we describe an augmented reality android-based idea in which we utilize augmented reality marker-based technology for augmenting newspaper advertisement with electronic information that does not modify the format of the newspaper document and remains exactly the same, substantially improves the utility of paper by reducing the portion of the printed Ad on the newspaper. An implementation on a camera phone is discussed that lets users retrieve data and access links from newspaper advertisements to electronic data. We carefully examined over twenty people of different ages and occupations who participated in the newspaper-based AR and we got a significant overall response. Further analysis implies that this may assist students in understanding the complex 3D objects, which they can manipulate, learn tasks and improve skills.